FLEXING DALAM SEDEKAH DI MEDIA SOSIAL Kajian Qs. Al-Baqarah [2]: 271 Prespektif Ma’na Cum Maghzā - Sahlan, Azis; Ma’ruf, Akhmad Rifa’i (Jurnal Studi Islam dan Sosial, 2023)
The recent phenomenon of flexing has become a hot topic, with not only influencers and YouTubers showcasing and flaunting their wealth but also the general public, including those in religious circles, being affected by flexing behavior, such as viralizing humanitarian and charitable activities. This has impacted the sincerity of those almsgiving or giving charity, resulting in both positive and negative consequences in their behavior. This research aims to analyze how Islam views the flexing phenomenon by exploring the meanings of open and hidden attitudes in giving charity in Surah Al-Baqarah [2]:271, using a qualitative method with a Ma’nā-cum-Maghzā approach. It dissects several aspects, including the Quranic perspective on the flexing phenomenon, principles of giving charity, limitations in displaying charity, and extracting the Maghzā from Surah Al-Baqarah [2]:271 related to the flexing phenomenon. The results of this research demonstrate that flexing behavior can lead to negative attitudes such as showing off (riyā’) and also motivations that can inspire the general public in the online world. Thus, there is a shift in meaning in Surah Al-Baqarah [2]:271, suggesting that while hidden charity is preferred (as a historical meaning), openly giving charity can also have virtues as long as it adheres to ethical principles in giving charity (as Maghzā).